2023
DOI: 10.26599/tst.2022.9010035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes as Potential Drug Targets for Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common cancers and ranks the third in cancer mortality all over the world. The goal of this study was to identify potential hub-genes, highlighting their functions, signaling pathways, and candidate drugs for the treatment of GC patients. We used publicly available next generation sequencing (NGS) data to identify differentially expressed (DE) genes. The top DE genes were mapped to STRING database to construct the protein-protein interaction (PPI) network and top hub gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Finally, we recommended our proposed BC-causing five upregulated (COL11A1, COL10A1, CD24, PLK1, UBE2C) and three down-regulated (PDK4, CD36, ACACB) HubGsguided top-ranked six ligands/molecules (Suramin, Rifaximin, Telmisartan, Tukysa Tucatinib, Lynparza Olaparib, TG.02) as the candidate drug molecules by molecular docking analysis. It should be mentioned here that both upregulated and down-regulated HubGs were used as drug targets in different studies [166][167][168][169]. Upregulated HubGs-guided drugs inhibit the upregulation of HubGs, while down-regulated HubGs-guided drugs activate the downregulation of HubGs [170].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we recommended our proposed BC-causing five upregulated (COL11A1, COL10A1, CD24, PLK1, UBE2C) and three down-regulated (PDK4, CD36, ACACB) HubGsguided top-ranked six ligands/molecules (Suramin, Rifaximin, Telmisartan, Tukysa Tucatinib, Lynparza Olaparib, TG.02) as the candidate drug molecules by molecular docking analysis. It should be mentioned here that both upregulated and down-regulated HubGs were used as drug targets in different studies [166][167][168][169]. Upregulated HubGs-guided drugs inhibit the upregulation of HubGs, while down-regulated HubGs-guided drugs activate the downregulation of HubGs [170].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that HC-056456, a CatSper channel blocker, as a novel ferroptosis-inducing compound inhibits GC cell growth by reducing GSH through the p53/SLC7A11 pathway, leading to increased Fe2+ and lipid peroxides in vitro and in vivo ( Zhang et al, 2022b ). In a comprehensive bioinformatic analysis of highly differentially expressed genes in GC, Hossain et al (2023) found that CDH2 , COL4A1 , and COL5A are associated with the survival of GC patients. They also identified docetaxel, lanreotide, venetoclax, temsirolimus, and nilotinib as the top six candidate drugs, targeting aforementioned proteins, for the treatment of GC patients ( Hossain et al, 2023 ).…”
Section: Repurposed Drugs For Gastrointestinal Cancers Treatmentmentioning
confidence: 99%
“…In a comprehensive bioinformatic analysis of highly differentially expressed genes in GC, Hossain et al (2023) found that CDH2 , COL4A1 , and COL5A are associated with the survival of GC patients. They also identified docetaxel, lanreotide, venetoclax, temsirolimus, and nilotinib as the top six candidate drugs, targeting aforementioned proteins, for the treatment of GC patients ( Hossain et al, 2023 ). Nitazoxanide also yielded favorable outcomes, as it exhibited activity across GC cell lines tested ( Ribeiro et al, 2023 ).…”
Section: Repurposed Drugs For Gastrointestinal Cancers Treatmentmentioning
confidence: 99%